Neuromedins U and S involvement in the regulation of the hypothalamo–pituitary–adrenal axis - Malendowicz, Ludwik K.; Ziolkowska, Agnieszka; Rucinski, Marcin (Frontiers in Endocrinology, 2012)
We reviewed neuromedin U (NMU) and neuromedin S (NMS) involvement in the regulation of the hypothalamo–pituitary–adrenal (HPA) axis function. NMU and NMS are structurally related and highly conserved neuropeptides. They exert biological effects via two GPCR receptors designated as NMUR1 and NMUR2 which show differential expression. NMUR1 is expressed predominantly at the periphery, while NMUR2 in the central nervous system. Elements of the NMU/NMS and their receptors network are also expressed in the HPA axis and progress in molecular biology techniques provided new information on their actions within this system. Several lines of evidence suggest that within the HPA axis NMU and NMS act at both hypothalamic and adrenal levels. Moreover, new data suggest that NMU and NMS are involved in central and peripheral control of the stress response.